2021
DOI: 10.1080/21655979.2021.1973877
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates chronic renal failure by targeting the PI3k/Akt pathway

Abstract: Chronic renal failure (CRF) threatens human health greatly and attracts worldwide concerns of health professionals in the public health sector. In our preliminary study, we found that Compound capsule (Shengqing Jiangzhuo Capsule, SQJZJN) had a significant therapeutic effect on CRF. Quercetin is one of the main components of this Compound capsule. In this study, we investigated the effect of Quercetin monomer on CRF and the regulation of PI3k/Akt pathway. Network pharmacology analysis methods were employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…The samples were then treated with IBA1 (1:1000), TSPO (1:1000), and P47 (1:1000) antibodies at 37°C for 2 h. Subsequently, the samples were treated with secondary antibodies Alexa Fluor 594, 488, and 674 (Thermo Fisher) for 45 min (room temperature). Finally, the samples were treated with DAPI at room temperature for 15 min and imaged using a confocal microscope (Olympus, Tokyo, Japan) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples were then treated with IBA1 (1:1000), TSPO (1:1000), and P47 (1:1000) antibodies at 37°C for 2 h. Subsequently, the samples were treated with secondary antibodies Alexa Fluor 594, 488, and 674 (Thermo Fisher) for 45 min (room temperature). Finally, the samples were treated with DAPI at room temperature for 15 min and imaged using a confocal microscope (Olympus, Tokyo, Japan) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intragastric administration of quercetin (1.5 and 3 g per kg body weight daily for eight weeks) effectively reduced apoptosis of renal cells and plasma levels of blood urea nitrogen, creatinine, and uric acid in male Sprague Dawley rat model of chronic renal failure [57]. The study also reported that quercetin treated rats showed reduced inflammation by preventing phosphoinositide 3-kinase (PI3 k)/Akt (protein kinase B) signaling pathway by targeting phosphoinositide 3-kinase regulatory subunit 1 (PIK3 R1) and reduced expression NLRP3, p-PI3 k, Phospho-Akt (p-Akt), and caspase1 in kidney tissues [57]. Another study reported that in a mouse model of renal dysplasia, quercetin treatment Interestingly, some antioxidants like flavonoids have been suggested as a complementary therapy for COVID-19 [50] and diabetes [51], which could be beneficial in ameliorating kidney damage during COVID-19 infection with diabetes as a comorbidity [52].…”
Section: Synergistic Kidney Damage and Morbidity Due To Covid-19 And ...mentioning
confidence: 99%
“…The flavonoid quercetin reportedly acts as a prophylactic to COVID-19 [55,56], as well as an antidiabetic and antioxidant compound. Moreover, recently, a preclinical study showed quercetin's renal protective effects [57]. Intragastric administration of quercetin (1.5 and 3 g per kg body weight daily for eight weeks) effectively reduced apoptosis of renal cells and plasma levels of blood urea nitrogen, creatinine, and uric acid in male Sprague Dawley rat model of chronic renal failure [57].…”
Section: Synergistic Kidney Damage and Morbidity Due To Covid-19 And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin has been reported to be critical to numerous fibrotic diseases. In vivo, quercetin inhibits PI3K/Akt pathway, thereby reducing renal fibrosis and apoptosis in CRF rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%